Evaluation of Malaria and Clinical Forms of Plasmodium Species in School Aged Children Attending Lokoja Specialist Hospital in Relation to Their Socioeconomic Status and Blood Group (Abo) Kogi State, Nigeria - J. S., Ngwamah; A., Mathias; Y.D., Dakum; K. B. , Shitta; H. , Audu-Ohida (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
Background: Malaria is a serious malady of public well-being issue, more especially among children of under-five years, pregnant women, and people with compromised immune system (such HIV and Tuberculosis patients ). It is an acute febrile illness caused by protozoan parasites of the genus Plasmodium that is disseminated by infected female Anopheles mosquito. The harmfulness of Plasmodium is associated with the amplitude of the infected red blood cells to adhere to some uninfected RBCs, a method called rosetting, which has been linked to occurrence of severe illness drug resistance and emergence of malaria after full treatment. The disease transmission is also associated with socio-economic status of an individual, environmental factors, climatic factors and seasons. Methods: A cross fragmentary hospital based study was accompanied on consenting the participants or their parents. Three hundred and thirty blood samples were collected, from which thin and thick Giemsa smears were prepared, and was scrutinized under a light microscope using 100X objective. The different blood types (ABO) were determined by adhesiveness using commercial antisera. Results: Out of the 330 children examined, 29 of them were found to be infected with malaria parasite. Twenty one were found to be infected with Plasmodium falciparum, while the remaining eight (8) infected individuals were found to be positive for P. malariae. In this study, female 15(9.38%) patients prove to be more infected than their male 14(8.24%) counterparts, even though statistically this finding revealed no significant difference (P>0.05) observed among the sexes. The results also depicts that children between 9-11 years had the highest incidence 15(14.29%) of malaria contagion, followed by those between age group 6-8 years old 5(11.11%), while children within age group 13-14 years old were list infected. In addition, the occupational information of the respondents shows that majority (45.76%) were civil servants, followed by traders (27.88%) and the least we're fisher men (10.61%). The result indicates that most of respondents were civil servants and traders. It is noticed that all participants were endangered to malaria infection. The fishermen proved to be more exposed to malaria risk factors. Conclusion: The study revealed that malaria infection is prevalent among the school aged children examined in the study area. It is a fact that malaria has negative impact on education, student growth and economy of the society. No any blood type, educational status, age group or occupational group that is immune to malaria infection once you are to bite of infected Anopheles mosquito you will definitely fall down with malaria. Prevention intervention and regular treatment with antimalarial drug is key to reduce the burden due to malaria. So the government and other stakeholders should equip the health facility of higher institutions with enough drugs, including antimalarial drug and also make sure each student have access to treated mosquito net. Also mass health education on possible ways of preventing malaria transmission should not be left out. Plasmodium, Malaria, Infection,